Diseño e implementación de una agenda telefónica en línea que permita al usuarío llamar a sus contactos desde una página web. - Juan León, Mera Mejía (2013)
This project involves the development of a Virtual Phonebook; same may be accessed by the client from any web browser. It allows calls between registered users, using any IP phone, with a single click and avoids the need to install additional plugins for its exclusive use. It also includes a collection system that is managed by buying virtual cards within the website, which must be deducted from client’s credit card, and the option to trigger a callback in case of the line is busy or the user is not available. The website was developed with PHP and Apache server mounted for display, while the call handling is done by Asterisk-base PBX. The merger of both parties was carried out using a MySQL database, allowing the use of Asterisk Real-Time Architecture (ARA) to create, modify or delete data in the PBX at runtime.